Implementation Of Work Discipline and Work Productivity On Employee Performance at PT Pelabuhan Indonesia (Persero) Regional I Belawan - Rachmawati, Yeni; Aprillia, Dini Tri; Surbakti, Eka Wulandari (Journal Boas : Business, Economics, Accounting And Management, 2023)
This study aims to find out how the implementation of work discipline and work productivity on employee performance at PT Pelabuhan Indonesia (Persero) Regional I Belawan. This type of research is quantitative research. The population and sample in this study were 36 people. Data collection techniques in this study using a questionnaire. The data analysis method used is multiple linear regression statistical analysis and uses the t test, f test and the coefficient of determination, while the instrument test uses validity and reliability tests with the help of SPSS version 26. Based on the results of this study indicate that work discipline and work productivity simultaneously ( f) test affects employee performance by using a significance of 0.000 <0.05 to obtain an F count of 78. 587 > from the value of F table 3.28. While partially (t test) shows that the work discipline variable has a significant effect on employee performance with a t count of 3.268 > t table of 2.034, the test is carried out using a sig value of 0.003 <0.05. While the work productivity variable shows that there is a significant influence on employee performance with a t value of 3,400 > t table value of 2.034.